Developing of HOTS-Based Pythagorean Theorem Questions in Mathematics Learning - N. Noerhasmalina; N. Nurmitasari (Peneliti.net, 2022)
The impact of question-based HOTS on learning Mathematics during a pandemic encourages students’ development of thinking skills and creativity. As a result, the aim of this research is to develop feasible HOTS-based Pythagorean Theorem questions in Mathematics learning. This type of research is development research design. This research development design is a 4-D development model. This 4-D development model is divided into four stages: define, design, develop, and disseminate. However, this research has only progressed to the stage develop. Based on the results of expert validation, it was found that HOTS-based Pythagorean Theorem questions were in correlated with the indicators of the feasibility’s questions to be applied. Then based on the test results using the correlation formula, Pearson product-moment found that the five items were valid, for the difficulty level the five items were included in the moderate criterion, for the distinguishing power that the five items had good distinguishing power, then using the formula it was alpha Cronbach determined that the five items are reliable. According to the research findings, HOTS-based Pythagorean Theorem questions are feasible to use for Mathematics instruction.